Unseen art : making, vision, and power in ancient Mesoamerica - Brittenham, Claudia (Austin : University of Texas Press, 2023)
"Claudia Brittenham is interested in understanding a puzzling phenomenon in Mesoamerican art history: why many of the objects that we now view in museums were, in their original contexts, extraordinarily difficult to see. We have become so used to seeing art, usually fully displayed when in a museum, that it is easy to forget how pieces of ancient art functioned and were situated within their original context. Many of these pieces had sacred and ritualistic purposes and therefore were placed in ways that allowed them to be only partially viewed, if at all, by the general public or by a select few. Brittenham posits that this was purposeful and imbued the objects with deep meaning for those who could view them, as well as ritualistic meaning for those who could not see the objects but understood this to be part of their importance. She examines Olmec buried offerings, Maya lintels, and carvings on the undersides of Aztec sculptures. The case studies she looks at are some of the most extreme examples of unseen art in Mesoamerica, offering new perspectives on some of the most charismatic of all Mesoamerican artworks. She argues that unseen art has important implications both for understanding the exercise of power in ancient Mesoamerica and for the practice of art history in the present"--
Introduction. Seeing and knowing -- Making : building community at La Venta -- Vision : seeing Maya lintels -- Power : carving the undersides of Aztec sculpture -- Conclusion. The language of Zuyua.
Includes bibliographical references and index.
Description based upon print version of record.
JSTOR
Keywords: Indians -- Antiquities; Indians -- Antiquities -- Religious aspects; Olmec art; Maya art; Aztec sculpture; Religious articles -- Central America; Religious articles -- Mexico; Ceremonial objects -- Central America; Ceremonial objects -- Mexico; Olmecs -- Rites and ceremonies; Mayas -- Rites and ceremonies; Aztecs -- Rites and ceremonies; Peuples autochtones -- Antiquités.; Peuples autochtones -- Antiquités -- Aspect religieux; Art olmèque.; Art maya; Sculpture aztèque.; Objets religieux -- Amérique centrale; Objets religieux -- Mexique; Objets rituels -- Amérique centrale; Objets rituels -- Mexique; Olmèques -- Rites et cérémonies.; Mayas -- Rites et cérémonies.; Aztèques -- Rites et cérémonies.; ART / General; Aztec sculpture; Aztecs -- Rites and ceremonies; Ceremonial objects; Indians -- Antiquities; Maya art; Mayas -- Rites and ceremonies; Olmec art; Religious articles; Central America; Mexico; Electronic books